Stability Constants and Antimicrobial Studies of Metal(II) Complexes with Cinnamaldehyde-(2-hydroxy benzylidene)hydrazide - Mittal, Pratibha; Uma, V. (Asian Journal of Chemistry, 2010)
Synthesis and structural features of some bidentate Schiff base complexes of the type [M(NNO)2] [where M = Cu2+, Ni2+, Co2+, Mn2+ and NNO = cinnamaldehyde-(2-hydroxy benzylidene)hydrazide] are reported. The ligand was derived by the condensation of cinnamaldehyde hydrazone with salicyaldehyde. These metal complexes were characterized by elemental analysis, molar conductance, magnetic momentum measurements, IR, 1H NMR spectral data. An octahedral geometry was proposed for all metal complexes. Stability constants of these metal complexes were determined using a potentiometric method at constant ionic strength (0.1 m) at different temperature (25, 30, 35 ºC) in 50 % v/v ethanol-water mixture by calculating the values of ηA, η and PL, has been found that ligand forms complexes in 1:2 ratio. Antimicrobial activities of ligand and its metal complexes were evaluated against strains- E. coli, Klebsiella, Enterococci and S. aureus. It has been found that metal complexes have higher activity than the parent ligand and their bio-potency are discussed.